2008
DOI: 10.2527/jas.2007-0394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dark storage and retail display on beef chuck and round muscles enhanced with ammonium hydroxide, salt, and carbon monoxide1,2

Abstract: The objective of this study was to determine the retail shelf stability of beef chuck and round muscles enhanced with ammonium hydroxide, salt, and carbon monoxide. A split plot design was used for each of 3 muscles [triceps brachii (TB), biceps femoris (BF), and rectus femoris (RF)] with 2 treatments (0 and 20% pump), 3 dark storage periods (1, 2, and 3 wk), and 3 replications in the whole plot and retail display period as the split plot. There were a total of 12 subprimals per treatment per dark storage peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 6 publications
5
13
1
Order By: Relevance
“…They concluded that one-third of the bacteria that grow at 25uC are unable to grow at 32uC after a 48-h incubation period (14). The pattern of bacterial growth we report in this study was also observed by Hamling et al (5). Their initial (2.58 versus 2.30 log CFU/g, respectively) and final (7.36 versus 8.13 log CFU/g, respectively) plate counts were similar to those in this study.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…They concluded that one-third of the bacteria that grow at 25uC are unable to grow at 32uC after a 48-h incubation period (14). The pattern of bacterial growth we report in this study was also observed by Hamling et al (5). Their initial (2.58 versus 2.30 log CFU/g, respectively) and final (7.36 versus 8.13 log CFU/g, respectively) plate counts were similar to those in this study.…”
Section: Resultssupporting
confidence: 88%
“…The antibacterial effect observed was attributed to the toxicity of AH rather than a change in pH (4). Hence, the results from Hamling et al (5) and Gupta et al (4), along with our results, suggest that AH slightly reduces psychrotrophic and mesophilic bacterial growth when used in the formulation of injection brine solutions.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…), as well as beef triceps brachii and rectus femoris steaks after seven days of retail display (Hamling et al . ). In addition, Naveena et al .…”
Section: Resultsmentioning
confidence: 97%
“…Enhancement of beef Triceps brachii , Biceps femoris and Rectus femoris with ammonium hydroxide, salt and CO resulted in greater color stability and higher total plate counts than non-enhanced steaks. Color stability of the enhanced steaks was improved by packaging in 100% CO 2 compared with packaging in 80% O 2 :20% CO 2 (Hamling et al ., 2008). Beef pretreated with 5% CO:95% N 2 for 24 h before VP was redder than controls without VP.…”
Section: Quality Improvement Through Packagingmentioning
confidence: 96%